Millet/peanut intercropping at a moderate N rate increases crop productivity and N use efficiency, as well as economic benefits, under rain-fed conditions - Zhu LIU; Zhen-wu NAN; Song-ming LIN; Hai-qiu YU; Li-yong XIE; Wei-wei MENG; Zheng ZHANG; Shu-bo WAN (Journal of Integrative Agriculture, 2023)
Cereal and legume intercropping has been widely adopted to increase crop productivity in sustainable farming systems worldwide. Among different intercropping combinations, millet and peanut intercropping can be adapted to most water-limited areas. However, there are few studies on the differences in yield characteristics and nitrogen use efficiency between millet/peanut intercropping and monocultures under different nitrogen (N) application rates. The objective of this study was to determine the yield advantages and economic benefits, as well as the appropriate N application rate, of millet/peanut intercropping. A two-year field experiment was conducted with three cropping patterns (monoculture millet, monoculture peanut and millet/peanut intercropping) and four N rates (0, 75, 150 and 225 kg ha−1). The results showed that the land equivalent ratio (LER) and net effect (NE) of the intercropping system reached their highest levels at the N input of 150 kg ha−1 in 2018 and 2019 (1.04 for LER, 0.347 Mg ha−1 for NE, averaged across two years). Millet was the dominant crop in the intercropping system (aggressivity of millet and peanut (Amp)>0, competitive ratio of millet and peanut (CRmp)>1), and millet yields achieved their highest values at N inputs of 225 kg ha−1 for monoculture and 150 kg ha−1 for intercropping. NUE reached its highest levels with N inputs of 150 kg ha−1 for all planting patterns over the two years. Intercropping combined with an N input of 150 kg ha−1 achieved the highest net income of 2 791 USD ha−1, with a benefit-cost ratio of 1.56, averaged over the two years. From the perspective of economics and agricultural sustainable development, millet/peanut intercropping at 150 kg N ha−1 seems to be a promising alternative to millet or peanut monoculture.